(3cJGH HbGA GdfaSs - (3GdWhSj, CHh LYaQ, fUjQ GdOjf, eMeO Hf eMeO Hf GdMSf, J (B672 (3g`s ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj dG jNjH ef HGHg Bed (B... (3agPg QSGdI MQQJgG aj Yde GdfaS hLYdJgG KdGKI aUhd, GdaUd GdChd aj GKHGJ Cf LhgQ GdfaS eZGjQ dLhgQ GdHOfs
(3BNQgG (B:s
(3BNQgG(B: (3hdcf dG jHYO Cf jaVj Hge GdCeQ Edi Cf jQJbhG Edi GdYGde GdYbdj hGdUbY GdEdgj hdG jecf TQMgG(B. (3hEPG bO hUdfG Edi gPG GdebGe hcTafG gPg GdCSQGQ adfcJa HgPG GdbOQ ef GdGSJHUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 30s
(3GdPQjYI, L (B3: 76s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs